THE DYNAMICS OF INTERPERSONAL RELATIONSHIPS AND THE INFLUENCE ON STUDENT LEARNING MOTIVATION AT MA MA'ARIF AL ASY'ARI - Laily Divia Amlati; Khumairo Wardatul Jannah; Risqi Dwi Cahyati (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study examines the phenomenon of students' emotional attraction at MA Ma'arif Al Asy'Ari which is often considered an obstacle to concentration, but psychologically has a strong influence on learning behavior. The main issue raised is the existence of rigid school policies on students' social relations, even though peer support is a key motivational factor. The purpose of this study is to map how the different interaction loci – internal and external to the school – affect the dynamics of student learning enthusiasm. Using a qualitative approach to phenomenological design, data were collected through participatory observation and in-depth interviews with teachers and students on April 22–23, 2026. The results show a pattern of impact dualism: the Internal-Class relationship functions as a positive catalyst through a mechanism of physical proximity (propinquity) that creates an intellectual "competition stage", where students perform self-equality in order to maintain an impression in front of the figure they admire. In contrast, the External-School relationship is destructive because it triggers "psychological energy leakage" and disorientation of priorities, leading to an increase in absenteeism because school is perceived as an inhibitor of outside interaction. The research discussion emphasized that the effectiveness of interpersonal motivation is highly dependent on the integration of these figures into the school ecosystem. In conclusion, an integrated relationship with the madrasah environment is able to turn emotional energy into academic encouragement, so the school needs to design an adaptive mentoring pattern by embracing the social dynamics of students as a positive force to achieve educational goals.